Review on mechanisms and structure-activity relationship of hypoglycemic effects of polysaccharides from natural resources - Xiaolong Ji; Jianhang Guo; Tengzheng Cao; Tingting Zhang; Yanqi Liu; Yizhe Yan (Food Science and Human Wellness)
Diabetes mellitus (DM) is a common multifactorial disease, causing various complications, such as chronic metabolism. The current therapies for diabetes mellitus are commercial diabetic drugs that have different definite side effect. However, polysaccharides mainly extracted from natural resources, have advantages of safety, accessibility, and anti-diabetic potential. We have summarized recent research of natural polysaccharides with hypoglycemic activities, focusing on different pharmacological mechanisms in various cell and animal models. The relationships of structure-hypoglycemic effect are also discussed in detail. This review could provide a comprehensive perspective for better understanding on development and mechanism of natural polysaccharides against diabetes mellitus, which have been required by clinical studies yet.